THE IDENTITY OF SHI‘A SYMPATHIZERS IN CONTEMPORARY INDONESIA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2008)
This paper sheds some light on Indonesian Shi‘a sympathizers, their particular relations among themselves as well as with others. Following the Iranian Revolution by the late 1970, Indonesian Muslims witnessed a remarkable religious enthusiasm marked by the proliferation of Shi‘a literature. This, in turn, is followed by the establishment of Shi‘a- based institutions, Islamic schools, publishers and associations over the regions. However, in a Sunni majority country like Indonesia, the identity of Shi‘a sympathizers is contested by various religious inclinations among themselves as well as with Indonesian Sunnis. Due to strong suspicion from the Sunnis, the outward appearance of Indonesian Shi‘i identity is not as visible as the Sunnis. It goes without saying that public discourse disappears. Some efforts to communicate with broader scope of Indonesian Muslims have been made by Shi‘a sympathizers, especially among new generations, in order to strengthen their community as well as carry out a more open and productive dialog with the Sunnis.